Patterns of drinking in Aboriginal and Torres Strait Islander peoples as self‐reported on the Grog Survey App: A representative urban and remote sample. (21st June 2021) - Zheng, Catherine; Conigrave, James H.; Conigrave, Katherine M.; Wilson, Scott; Perry, Jimmy; Chikritzhs, Tanya N.; Fitts, Michelle S.; Lee, K. S. Kylie
Abstract: Introduction: Measuring self‐reported alcohol use is challenging in any population, including when episodic drinking may be common. Drinking among Indigenous Australians has been shown to vary greatly within and between communities. However, most survey methods assume 'regular' patterns of drinking. National estimates have also been shown to underestimate alcohol use among this group. This paper describes drinking patterns in two representative community samples (urban and remote). Methods: Indigenous Australians (aged 16+ years) in two South Australian sites were recruited to complete the Grog Survey App. The App is a validated, interactive tablet‐based survey tool, designed to help Indigenous Australians describe their drinking. Drinking patterns were described using medians and interquartile ranges; gender and remoteness were compared using Wilcoxon rank‐sum tests. Spearman correlations explored the relationship between drinking patterns and age. Logistic regressions tested if beverage or container preference differed by remoteness or gender. Results: Three‐quarters of participants (77.0%, n = 597/775) were current drinkers. Median standard drinks per occasion was 7.8 (78 g), 1.3 drinking occasions per month (median). Three‐quarters of current drinkers (73.7%) reported a period without drinking (median: 60 days). Remote drinkers were more likely to drink beer. Improvised containers were used by 40.5% of drinkers. Discussion and Conclusions: Episodic drinking with extended 'dry' periods and from non‐standard drinking containers was common in this representative sample of Indigenous Australians. The diversity of container use and beverage preference, by gender and remoteness, illustrates nuances in drinking patterns between communities. It shows the importance of community‐level data to inform local strategies addressing alcohol misuse.